Biological Interaction Between Copper(II) Complex and Nucleosides - Guo, Yaping; Wang, Xiuju; Luo, Leiming; Du, Jinge; Shang, Xuefang (Asian Journal of Chemistry, 2014)
A copper-coordinated complex based on 7-membered amide cycle has been designed and synthesized. Its binding properties for various nucleosides, guanosine-5'-diphosphate (GDP), uridine-5'-diphosphate (UDP), inosine-5'- diphosphate (IDP) and guanosine-5'-triphosphate (GTP) has been studied by UV-visible spectra and crystal structure. Results indicated that the compound showed the highest binding ability with guanosine-5'-triphosphate in water solution among the studied nucleosides. The interaction of host-guest derived from hydrogen bonding and p-p staking and the host-guest binding ability depended on the chain length of nucleosides. In addition, the compound can be used to label nucleoside.